Triumphs and Tribulations of Teaching Practicum Experiences: Reflections from Preservice Teachers in UAE - Laila Mohebi (University of Bologna, 2023)
The 'Practicum-3' preservice teachers are those who are in their 3rd year of their degree studies and have prior teaching experience. The intent of this qualitative paper is to assess the challenges experienced by the preservice teachers and the tactics used by them to manage these challenges, during their first week of teaching practice. The challenges reported herein were thematically analysed after extrapolating from the participants' narratives and presented within the context of the Gibbs' Reflective Cycle. Findings from this study reveal that there are several factors within and outside the control of the student teacher that affect the practicum experience. Further, the preservice teacher's preparedness and emotional disposition significantly influence discharge of the duty. In the same vein, the mentor-mentee relations contribute a lot in making or breaking the practicum experience for student teachers in the UAE. The findings recommend further explorative assessments of the situation and necessary policy corrections in the preservice teacher education.